(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
Rape is one of the most heinous crimes against women. The offence of rape in its simplest term is “the ravishment of a woman, without her consent, by force, fear or fraud”, or as “the carnal knowledge of a woman by force against her will”*). In spite of strict laws against rape and the consequent punishment, it still remains a serious problem. In India, it is extremely difficult to prove the charges of rape against a person in a court of law. Generally, in any criminal trial, independent corroboration may be necessary before establishing guilt. But, in case of rape if the statement of victim found to be worthy of credence and reliable, requires no corroboration. The court may convict the accused on the sole testimony of the victim. However, a lot of weightage is given to forensic evidence and therefore such evidence can help to convict the guilty. Thus, a doctor can help in providing the necessary corroborative medical evidence to prove a case of rape. A doctor’s opinion is independent and scientific and therefore it not only corroborates the crime but may also help an innocent person who has been wrongly implicated.